A Comparative Study of the Aesthetic Outcome of Two Techniques for Unilateral Complete Cleft Lip Repair. Issue 4 (October 2017) - Phillips, Georgina S. A.; Swan, Marc C.; Sawyer, Adam R.; Goodacre, Tim E. E.; Cadier, Michael
Abstract : Background: Cleft lip repair aims to create symmetric nasolabial morphology with minimal scarring. Poor aesthetic outcomes may have damaging psychosocial implications. Determining the optimal method of recreating lip symmetry is a major goal of applied cleft clinical research. This study aims to determine whether subjective assessment could differentiate aesthetic outcome between two surgeons who use two different surgical techniques for unilateral cleft lip repair. Methods: Surgeon A uses a modified rotation-advancement technique incorporating a supra–white roll flap and Noordhoff-style vermilion flap. Surgeon B uses an upper and lower triangle technique. Neither surgeon used presurgical orthopedics. Five-year postoperative frontal photographs (cropped according to the Asher-McDade aesthetic index) were analyzed by a panel of 40 blinded surgical and lay reviewers using a five-point Likert scale. The assessments were repeated after a 2-week interval to assess intrarater reliability. Results: Thirty-nine consecutive complete unilateral cleft lip and palate patients were assessed for each surgeon. The mean Likert score for surgical/lay assessors was 3.07/3.00 for surgeon A and 2.67/2.61 for surgeon B. This difference was statistically significant ( p < 0.05). The interrater reliability was excellent and the intrarater reliability was fair. There was good correlation between lay and surgical assessors. Conclusion: Subjective assessment of clinical photography provides a reliable method of differentiating aesthetic outcome after unilateral cleft lip repair and presents a rapid and straightforward clinically relevant method of comparing surgical outcomes.